A model for cosmological simulations of galaxy formation physics: multi-epoch validation. Issue 3 (9th January 2014) - Torrey, Paul; Vogelsberger, Mark; Genel, Shy; Sijacki, Debora; Springel, Volker; Hernquist, Lars
Abstract : We present a multi-epoch analysis of the galaxy populations formed within the cosmological hydrodynamical simulations presented in Vogelsberger et al. These simulations explore the performance of a recently implemented feedback model which includes primordial and metal line radiative cooling with self-shielding corrections; stellar evolution with associated mass-loss and chemical enrichment; feedback by stellar winds; black hole seeding, growth and merging; and active galactic nuclei (AGN) quasar- and radio-mode heating with a phenomenological prescription for AGN electro-magnetic feedback. We illustrate the impact of the model parameter choices on the resulting simulated galaxy population properties at high and intermediate redshifts. We demonstrate that our scheme is capable of producing galaxy populations that broadly reproduce the shape of the observed galaxy stellar mass function extending from redshift z = 0 to z = 3. We also characterize the evolving galactic B -band luminosity function, stellar mass to halo mass ratio, star formation main sequence, Tully–Fisher relation and gas-phase mass–metallicity relation and confront them against recent observational estimates. This detailed comparison allows us to validate elements of our feedback model, while also identifying areas of tension (e.g., the shape and normalization of the mass–metallicity relation and normalization of the star formation main sequence) that will be addressed in future work.